Matching gerontechnologies to independent-living seniors' individual needs: development of the GTM tool - Marc Haufe; Sebastiaan Theodorus Michaël Peek; Katrien Ger Luijkx (BMC, 2019)
Abstract Background Most seniors wish to live independently for as long as possible. Gerontechnologies such as personal alarms or remote control systems, have the potential to help them age in place. For seniors, assessing what is the most appropriate technology for their aging in place needs can be difficult. Professionals specifically tasked with matching seniors' needs with technology solutions can greatly help here. Yet not much is known about the challenges these professionals face or how they can optimize their matchmaking service. Methods Participatory action research was conducted in the Netherlands, in two phases. In phase one, ten matchmaking dialogues between municipal technology consultants and seniors were observed, followed by interviews with both technology consultants and seniors to understand the current matchmaking service. In phase two, a new matchmaking tool was co-created with technology consultants and other professionals over the course of four co-creation session. Variants of the tool were tested out in nine additional matchmaking dialogues. The Cycle of Technology Acquirement by Independent-Living Seniors (C-TAILS) model, which can be used to understand both origins and consequences of technology acquirement by independent-living seniors, was used as a theoretical lens. Results Important challenges for municipal technology consultants in their current matchmaking practice are: making the matchmaking service more demand oriented and creating an accurate and complete overview of relevant factors within the seniors' individual situation so that an optimal match can be made. Together with technology consultants and other professionals, a new Gerontechnologies Matchmaking (GTM) tool was created to help overcome these challenges. Evaluation of the tool showed that it better includes each senior's personal, social, physical and technological context, within the matchmaking service. Conclusion Professionals who help seniors match gerontechnology to their aging in place needs experience a variety of challenges in the delivery of their service. Currently, few tools are available for them to overcome these challenges. The newly developed GTM tool can help overcome challenges and optimize matchmaking services. Further testing of the tool in different contexts is needed to determine its generalizability.